A Method for Generating Mouse Model of Stroke: Evaluation of Parameters for Blood Flow, Behavior, and Survival - Park, Sin-Young; Marasini, Subash; Kim, Geu-Hee; Ku, Taeyun; Choi, Chulhee; Park, Min-Young; Kim, Eun-Hee; Lee, Young-Don; Suh-Kim, Haeyoung; Kim, Sung-Soo (Experimental neurobiology, 2014)
Stroke is one of the common causes of death and disability. Despite extensive efforts in stroke research, therapeutic options for improving the functional recovery remain limited in clinical practice. Experimental stroke models using genetically modified mice could aid in unraveling the complex pathophysiology triggered by ischemic brain injury. Here, we optimized the procedure for generating mouse stroke model using an intraluminal suture in the middle cerebral artery and verified the blockage of blood flow using indocyanine green coupled with near infra-red radiation. The first week after the ischemic injury was critical for survivability. The survival rate of 11% in mice without any treatment but increased to 60% on administering prophylactic antibiotics. During this period, mice showed severe functional impairment but recovered spontaneously starting from the second week onward. Among the various behavioral tests, the pole tests and neurological severity score tests remained reliable up to 4 weeks after ischemia, whereas the rotarod and corner tests became less sensitive for assessing the severity of ischemic injury with time. Further, loss of body weight was also observed for up 4 weeks after ischemia induction. In conclusion, we have developed an improved approach which allows us to investigate the role of the cell death-related genes in the disease progression using genetically modified mice and to evaluate the modes of action of candidate drugs. KCI Citation Count: 0